2011
DOI: 10.1007/s12264-011-1048-y
|View full text |Cite
|
Sign up to set email alerts
|

Potassium channel blockers as an effective treatment to restore impulse conduction in injured axons

Abstract: Most axons in the vertebral central nervous system are myelinated by oligodendrocytes. Myelin protects and insulates neuronal processes, enabling the fast, saltatory conduction unique to myelinated axons. Myelin disruption resulting from trauma and biochemical reaction is a common pathological event in spinal cord injury and chronic neurodegenerative diseases. Myelin damage-induced axonal conduction block is considered to be a significant contributor to the devastating neurological deficits resulting from trau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 73 publications
(136 reference statements)
1
39
0
1
Order By: Relevance
“…Additionally, a simulation with mutant-urotoxin (Lys25Ala) indicated that Lys25 does not have the same role in the binding of urotoxin to hK v 1.2 as in other a-KTx-6 toxins. Our results suggest that urotoxin may be useful as a pharmacologic tool to reveal the physiologic function of hK v 1.2 channels in in vitro and in vivo experiments, as a lead for peptidomimetics for the targeting of hK v 1.2 channels, and as an experimental therapeutic tool to restore axonal conduction in demyelinated axons, where inhibition of K 1 channels has beneficial effects (Beraud et al, 2006;Shi and Sun, 2011).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Additionally, a simulation with mutant-urotoxin (Lys25Ala) indicated that Lys25 does not have the same role in the binding of urotoxin to hK v 1.2 as in other a-KTx-6 toxins. Our results suggest that urotoxin may be useful as a pharmacologic tool to reveal the physiologic function of hK v 1.2 channels in in vitro and in vivo experiments, as a lead for peptidomimetics for the targeting of hK v 1.2 channels, and as an experimental therapeutic tool to restore axonal conduction in demyelinated axons, where inhibition of K 1 channels has beneficial effects (Beraud et al, 2006;Shi and Sun, 2011).…”
Section: Introductionmentioning
confidence: 90%
“…Knowledge of the interacting surfaces between the channels and toxins may allow the design of specific drugs to control pathologies associated with K 1 channels, such as demyelinating diseases (e.g., Guillain-Barré syndrome, multiple sclerosis) and Lambert-Eaton myasthenic syndrome (Judge and Bever, 2006;Shi and Sun, 2011).…”
Section: Characterization Of the Potassium Channel Blocker Urotoxinmentioning
confidence: 99%
“…Myelin enhances axonal conduction by both inhibiting ionic exchange across the membrane and increasing transverse resistance at the internodal region [12]. Accordingly, compromise of the structural integrity of myelin elicits significant conduction loss in spinal cord tissue partly due to the exposure and consequential activation of voltage-gated K + channels typically residing in the juxtaparanodal region [1, 10, 11, 1315]. Ex vivo studies of spinal cord tissue have demonstrated that myelin damage and subsequent exposure of K + channels impaired signal propagation, indicated by a reduction of compound action potential (CAP) amplitude [10, 11, 14].…”
Section: Pathological Significance Of Myelin Damage In Cns Trauma Andmentioning
confidence: 99%
“…In the case of trauma, primary injury mediated by physical forces triggers subsequent pathological molecular mechanisms, deemed secondary injury [22, 23]. Separation of these two components was postulated decades ago and has been supported by many subsequent studies [13, 22, 23]. Recently, this phenomenon was demonstrated in an ex vivo acute spinal cord injury model where a mechanical stretch injury resulted in immediate myelin damage indicated by lengthening of the nodal region and retraction of myelin from the paranodal region following the physical insult [11].…”
Section: Mechanisms Of Myelin Damagementioning
confidence: 99%
“…These studies have raised a possibility that neuronal tracers may fail to fully illuminate those damaged (but structurally connected) axons, at least transiently and during the early phase of injury, potentially confounding the use of serial labeling approaches to argue for regeneration. Others have reported that surviving but compressed axons may also be physiologically abnormal for a certain period of time, probably due to altered myelin structure and potassium channel activity, leading to conduction failure and loss of function (Nashmi & Fehlings, 2001; Shi & Sun, 2011). …”
Section: Commonly Used Strategies Are Not Sufficientmentioning
confidence: 99%